United Arab Emirates : Financial System Stability Assessment. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
This Financial System Stability Assessment on the United Arab Emirates (UAE) examines macroeconomic and financial sector developments. The banking sector as a whole shows comfortable levels of capitalization and profits, having benefited from the rapid expansion of the economy and a steady decline in the ratio of nonperforming loans (NPLs) to total loans. Although mortgages still account for a relatively small part of bank loan portfolios, the indirect exposure could be significant. Some financial institutions' lending standards also may be weakening as they compete for new business in mortgage lending.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet